Analysis On Worker Productivity At SKPD B6 Office Building Construction Project In Kelurahan Sail Kecamatan Tenayan Raya Pekanbaru - Winson Enrique H; Rian Trikomara; Hendra Taufik (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Worker productivity greatly impacts the success of construction projects. Therefore, it is imperative to perform analysis on the determination of worker productivity. The worker productivity on the column, beam, and floor slab rebar detailing, formwork, and concrete casting process were observed directly on the field. The field observations were intended to measure the time required to complete a specified amount of tasks, so the necessary amount of work hours per day to finish the entire work could be determined. The time values obtained from the observations were then processed to determine the productivity coefficient of workers for each tasks. Based on the analysis results, the productivity coefficient for column rebar detailing task was 0.035 for worker, 0.015 for rebar detailer, and 0.005 for supervisor. For column formwork task, the productivity coefficient was 0.083 for worker, 0.125 for carpenter, and 0.042 for supervisor. For column concrete casting task, the productivity coefficient was 0.194 for worker, 0.097 for skilled worker, and 0.097 for supervisor. For beam rebar detailing task, the productivity coefficient was 0.065 for worker, 0.043 for rebar detailer, and 0.011 for supervisor. For beam formwork task, the productivity coefficient was 0.127 for worker, 0.085 for carpenter, and 0.042 for supervisor. For beam concrete casting task, the productivity coefficient was 2.268 for worker, 0.567 for skilled worker, and 0.567 for supervisor. For floor slab rebar detailing task, the productivity coefficient was 0.020 for worker, 0.020 for rebar detailer, and 0.005 for supervisor. For floor slab formwork task, the productivity coefficient was 0.521 for worker, 0.347 for carpenter, and 0.174 for supervisor. For floor slab concrete casting task, the productivity coefficient was 1.705 for worker, 0.426 for skilled worker, and 0.426 for supervisor.Keywords: productivity, coefficient, workers, supervisor, floor slab